(untitled) (Revista de Biología Marina y Oceanografía, 2020)
Information on selected bio-optical properties and primary production values of the waters of the Bay of La Paz, southern Gulf of California, is reported during June 2004, a region characterized to have very rich biodiversity, including endemic and endangered species, with high ecological relevance. In-situ measurements of natural fluorescence and photosynthetically available radiation (PAR) enabled the subsequent calculation of the incident irradiance (E0), the light extinction coefficient (k), compensation depth (Zc) and critical depth (Zcr). The results suggest the presence of light propitious conditions for phytoplankton community growth and net primary production, which are highly significant for the potential development of models of light penetration, ocean color, primary productivity, and analyses of organic carbon energy flow.